Temporal Response of Bacterial Community Associated Fe(III) Reduction to Initial pH Shift of Paddy Soils - Rong Jia; Fangmei Fan; Lina Li; Dong Qu (Agronomy, 2022)
The temporal response of bacterial community, especially that of bacteria with Fe(III) reducing ability, in flooded paddy soils to initial pH changes, is not well-documented. This work demonstrated variations in concentration of Fe species, bacterial activity and community succession in paddy soils with initial pH shift to acidic or alkaline level. The causal links of pH shift-induced bacterial community succession with Fe(III) reduction was also assessed. Results showed that soil initial pH shifts greatly influenced bacterial community and Fe(III) reduction. A soil pH shift from acidic to alkaline level enhanced bacterial abundance and dehydrogenase activity (DHA), which accordingly caused an increase in Fe(III) reducing ratio by 22.26% on day One of flooding. The stimulated putative Fe(III) reducing species, Bacillus and Solibacillus, caused stimulation of Fe(III) reduction with pH increase. However, there was continuous inhibition of Fe(III) reduction with a pH shift from alkaline to acidic, with Fe(III) reducing ratios decreased by 11.98–40.04%. The inhibited DHA and Fe(III) reducing bacteria were amenable for the suspension of Fe(III) reduction. This study suggests that bacterial activity and Fe(III) concentration, in responses to initial soil pH shift, are primarily responsible for pH shift-induced Fe(III) reduction in paddy soils.